The rehabilitation of children with brain tumors using exergames: a scoping review protocol - Catarina Dias Ribeiro; Pedro José Moreira Barbosa; Sandra Sofia Barbosa Pinto de Almeida; Goreti Filipa dos Santos Marques; José Miguel dos Santos Castro Padilha (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: To map the literature on the use of exergames in the rehabilitation of school-age children with brain tumors, in any context. Method: Scoping review protocol developed using the recommendations of the Joanna Briggs Institute. The search will include aggregators, databases, indexes, repositories, and research browsers, without limitation as to the year of publication. Primary and secondary studies that include school-age children with brain tumors and that use exergames in children's motor rehabilitation in any context will be eligible. The selection and extraction of data will be carried out by two independent researchers and, if necessary, a third researcher will resolve any discrepancies. Results: The data analyzed will be presented in diagrammatic, tabular, and descriptive form. Final considerations: The mapping of interventions using exergames in the rehabilitation of school-age children with brain tumors could lead to reflection on the main components to be considered in intervention programs, supporting informed nursing decision-making and identifying the main areas of interest for research. It is hoped that the results of this review can contribute to strengthening knowledge in this field, promoting a better quality of life for children with brain tumors, as well as for their families.